N-linoleyltyrosine resisted the growth of non-small cell lung cancer cells via the regulation of CB1 and CB2 involvement of PI3K and ERK pathways - Hu, Yan; Zhao, Zhe; Liu, Yuan-Ting; Xu, Ze-Cheng; Li, Jing-Yi; Yang, Zheng-Yu; Rui-Wang,; Yang, Yun-Qi; Zhang, Jia-Hui; Qiu, Si-Yuan; He, Tao; Wu, Yi-Ying; et al. (Frontiers in Pharmacology, 2023)
N-linoleyltyrosine (NITyr), one of the anandamide analogies, exerted activities via the endocannabinoid receptor (CB1 and CB2), and endocannabinoid receptor showed anti-tumor effects in diverse tumors. Therefore, we speculated that NITyr might show anti-NSCLC effects via CB1 or CB2 receptor. The purpose of the investigation was to reveal the anti-tumor ability of NITyr on A549 cells and its mechanisms. The viability of A549 cells was measured by MTT assay, the cell cycle and apoptosis were both examined by flow cytometry, besides, the cell migration was tested by wound healing assay. Apoptosis related markers were measured by western blotting. The downstream signaling pathway of CB1 or CB2 was examined through western blotting. The expressions of CB1 and CB2 were detected by immunofluorescent staining. We found that NITyr inhibited the cell viability, hindered the cell cycle, resulted in apoptosis and inhibited migration. Western blot analysis indicated that NITyr upregulated the expressions of p-PI3K and p-ERK and didn’t affect p-JNK expression. Immunofluorescence assay suggested that NITyr upregulated the expressions of CB1 and CB2. In conclusion, NITyr showed an effect of inhibiting NSCLC by boosting apoptosis through the activation of CB1 and CB2 receptor involved in PI3K and ERK pathway.